BIOCHEMICAL CHANGES IN CHICKPEA ROOTS AFTER INOCULATION WITH VIRULENT AND HYPOVIRULENT. ISOLATES OF FUSARIUM OXYSPORUM F. SP. CICERIS (Biological Sciences - PJSIR, 2004)
Total phenolic contents increased in the roots of susceptible and resistant varieties of chickpea after inoculation with the virulent as well as hypovirulent isolates of Fusarium oxysporum f. sp. ciceris (FOC). Highest increase was observed against the highly virulent isolate 9718 in the roots of Aug - 424 and CM 98. While least increase was found against less virulent isolates viz. 2002 and 2014. Increases in total phenols were more in resistant variety as compared to susceptible one. Inhibition of total phenols was observed in the roots of both varieties nine days after germination by the isolates 2012, 9718 and 2002. No reduction in phenols of both varieties was observed against less virulent isolate 2014. The biautography of the developed TLC by using Cladosporium cucumerinum revealed that two inhibition zones were produced by both the varieties against all the FOC isolates. Highest expression of total phenols in chickpea roots was found by the most virulent isolate 9718 followed by 2012 and 2002, reduction was more in CM 98 as compared to Aug - 424. The results suggest that the virulent and hypovirulent isolates produced non-specific elicitors while specific suppressors were produced by the isolates 9718, 2012 and 2002.